ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. H DI WILAYAH KERJA PUSKESMAS SUNGAI JINGAH KECAMATAN BANJARMASIN UTARA - Lilyanti Maya Sari; Muflihah; Nur Cahyani Ari Lestari (Universitas Batam, 2023)
PWS-KIA recapitulation data at Sungai Jingah Health Center in 2020 total coverage of pure K1 is 687 people (61.8%) of the target 1,110 people (100%), K1 access is 1,096 people (98.5%) while K4 is 1,042 people (93, 7%) with a target of 1,110 people (100%) Research method used is descriptive research with case study method. The research was conducted at Sungai Jingah Health Center Banjarmasin Barat, and took place from October 2020 - December 2021. The subject used in this case study with midwifery care management was Mrs. H G1P0A0 37 weeks pregnant which was given comprehensively from pregnancy, childbirth, postpartum, newborn and family planning in the Sungai Jingah Community Health Center, Banjarmasin..On the results of the Final Project Report (LTA) with Comprehensive Midwifery: Subjective and objective data on care for pregnancy, childbirth, newborns, postpartum and family planning on Ny. H has been collected. Subjective and objective data on the care of pregnancy, childbirth, newborns, postpartum and family planning on Ny. H has been interpreted. Based on subjective and objective data on the care of pregnancy, childbirth, newborns, postpartum and family planning on Ny. H can be drawn assessment or diagnosis in all care is physiological. Based on the data analysis, there is no need for immediate action for collaboration and referral to care for pregnancy, childbirth, newborns, postpartum and family planning on Ny. H. The management has been arranged in accordance with the care provided for both pregnancy, childbirth, newborn, postpartum and family planning care for Mrs. H